2020
DOI: 10.1101/2020.05.14.089805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multistability in cellular differentiation enabled by a network of three mutually repressing master regulators

Abstract: Identifying the design principles of complex regulatory networks driving cellular decision-making remains essential to decode embryonic development as well as enhance cellular reprogramming. A well-studied network motif involved in cellular decision-making is a toggle switch -a set of two opposing transcription factors A and B, each of which is a master regulator of a specific cell-fate and can inhibit the activity of the other. A toggle switch can lead to two possible states -(high A, low B) and (low A, high … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Similarly, distribution within the bistable states is broadly conserved: for the 5-component network, all bistable phases (the combination of steady states) formed as a combination of any of the ten dominant monostable states together have a frequency of about 80% (Fig 6B). The dominance of these bistable states as a combination of any of the dominant monostable states continues for 7-component (Fig 6B ) and, 9-component (Fig S6A) toggle polygon as well, thus resonating with our previous observation for the toggle triad network [18].…”
Section: Figure 5: Odd-numbered Toggle Polygons Comparison Between the Most Frequent Solutions Of The Different Odd-element Toggle Polygosupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, distribution within the bistable states is broadly conserved: for the 5-component network, all bistable phases (the combination of steady states) formed as a combination of any of the ten dominant monostable states together have a frequency of about 80% (Fig 6B). The dominance of these bistable states as a combination of any of the dominant monostable states continues for 7-component (Fig 6B ) and, 9-component (Fig S6A) toggle polygon as well, thus resonating with our previous observation for the toggle triad network [18].…”
Section: Figure 5: Odd-numbered Toggle Polygons Comparison Between the Most Frequent Solutions Of The Different Odd-element Toggle Polygosupporting
confidence: 88%
“…Next, we focused on odd-numbered toggle polygons. Our previous simulations showed that a toggle triad network could converge to one of the six dominant states: three 'single-positive' ones (only one of the nodes of the network is high, other two are low -(A, B, C) = (1, 0, 0), (0, 1, 0) or (0, 0, 1)) and the three 'double positive' ones (two of the nodes in the network are high -(A, B, C) = (1, 0, 1), (0, 1, 1), (1, 0, 1)) [18]. We next analyzed the steady states of higher order oddnumbered toggle polygon networks to find similarities and differences with trends seen for toggle triad.…”
Section: Design Principles Of Odd-numbered Toggle Polygonsmentioning
confidence: 99%
See 1 more Smart Citation
“…We define a link-strength metric similar to the one used earlier [95] to quantify the strength of each link independent of its activation at steady state. The link strength ( !…”
Section: Link Strength Metricsmentioning
confidence: 99%
“…Next, we focused on odd-numbered toggle polygons. Our previous simulations showed that a toggle triad network could converge to one of the six dominant states: three ‘single-positive’ ones (only one of the nodes of the network is high, other two are low – (A, B, C) = (1, 0, 0), (0, 1, 0) or (0, 0, 1)) and the three ‘double positive’ ones (two of the nodes in the network are high – (A, B, C) = (1, 0, 1), (0, 1, 1), (1, 0, 1)) [18]. We next analyzed the steady states of higher order odd-numbered toggle polygon networks to find similarities and differences with trends seen for toggle triad.…”
Section: Resultsmentioning
confidence: 99%